1986
DOI: 10.1017/s0889189300001223
|View full text |Cite
|
Sign up to set email alerts
|

An economic analysis of alternative cropping systems for east-central Nebraska

Abstract: Thirteen cropping systems were analyzed with respect to profitability and risk for east-central Nebraska. The systems were developed from 1) a four-year rotation containing a small grain, 2) two row crop rotations, 3) three continuous cropped alternatives, and 4) combinations of continuous cropped alternatives. Three systems were developed from the four-year rotation including two alternative treatments of inorganic chemicals as well as an organic alternative. Eight years of experimental yields, historical pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…Since our budgets were based on assumed conditions after the yield transition stage has passed, the estimates of alternative system yields may be conservative. However, our assumed differences between alternative and conventional system yields are generally consistent with reports by such authors as Helmers et al (1986) and Lockeretz et al (1981). Some other reports indicate that alternative system yields eventually equal conventional system yields, after the transition phase has passed (e.g., U.S. Department of Agriculture, 1980).…”
Section: Studies Of Farming Systems At Southsupporting
confidence: 90%
See 1 more Smart Citation
“…Since our budgets were based on assumed conditions after the yield transition stage has passed, the estimates of alternative system yields may be conservative. However, our assumed differences between alternative and conventional system yields are generally consistent with reports by such authors as Helmers et al (1986) and Lockeretz et al (1981). Some other reports indicate that alternative system yields eventually equal conventional system yields, after the transition phase has passed (e.g., U.S. Department of Agriculture, 1980).…”
Section: Studies Of Farming Systems At Southsupporting
confidence: 90%
“…However, a few such studies have been reported in this journal (e.g., Helmers et al, 1986;Domanico et al, 1986; Dabbert and Madden, 1986; and Goldstein and Young, 1987) and elsewhere (e.g., Shearer et al, 1981;Duffy, 1987;. These reflect an important initial effort to build an information base on the economics of alternative farming systems.…”
Section: Introductionmentioning
confidence: 86%
“…Crop rotations reduce the risk of disease, insect attack, weeds, and crop failure risk associated with monoculture (Helmers et al, 1986;Karlen et al, 1994), with resulting improvements in crop yield (Pierce and Rice, 1988). The use of N fertilizers changed the natural cycling of C and N in the field, which was previously managed by the legume rotations, fallow periods, and applications of manure.…”
Section: Crop Rotationsmentioning
confidence: 99%
“…A review of recent studies (Daberkow, et al, 1988;Domanico, et al, 1986;Helmers, et al, 1986;Dabbert and Madden, 1986; and Goldstein and Young, 1987) involving a variety of commodities and locations reveals a wide range of results on profitability of and, hence, incentives to adopt, low-input, environmentally sustainable agriculture. With the exception of oilseeds, these same commodities are among the major beneficiaries of the highly distortive subsidies and acreage reduction programs.…”
Section: Current Trade Policy and Us Agriculturementioning
confidence: 99%